State of aggregations and biological characteristics for mysid Neomysis awatschensis in the northern Amur Bay (Peter the Great Bay, Japan Sea) - L. G. Sedova; L. L. Budnikova (Известия ТИНРО)
Size and sex structure of estuarine-freshwater mysid Neomysis awatschensis in the northern Amur Bay is considered, time of their aggregations formation is determined, and their biomass is estimated on the data of surveys conducted in 2014–2019. The samples were collected at the depth of 0.5–2.0 m in the daytime in May-July. The catches were recalculated per 1 m3 of water. All collected mysids (2212 ind.) were measured under binocular microscope with accuracy of 0.1 mm, weighted by torsion scales with accuracy of 1 mg, and separated to males, females and juveniles. The females were differentiated by 5 stages of their development: 1) immature females with oostegetic rudiments; 2) oviparous females; 3) females with embryos in the marsupia bags without stalk-eyes with black pigment; 4) females with embryos in marsupia bags with black eyes; 5) spawned females with empty marsupii. Time and duration of N. awatschensis aggregating changed by years in dependence on hydrological and weather conditions; the aggregations were either monospecific or mixed with another mysid species — N. mirabilis. The maximum mysid biomass could exceed 500 g/m3 that was appropriate for commercial fishery. The maximum body length of mysid females was 13.7 mm, of males — 12.0 mm. The average length varied from 6.7 to 10.3 mm, being shorter in summer months than in May. Portion of males in the aggregations was always significant (16.3–50.7 %), portion of females varied from 8.7 to 52.5 %, portion of juveniles was the largest in June (29.9–75.0 %). The females to males ratio was 1 : 1 in May and July of 2014–2017, but males prevailed in June 2015 (1.0 : 1.9), whereas females prevailed in June 2016 (1.8 : 1.0). Spawning of the mysids was the most intensive in May-June, though females had embryos at different stages of development in all samples that indicated an extended period of reproduction.